Cobalt mediated by desulfurization toward the synthesis of isothiocyanates. Issue 21 (1st November 2016) - Seelam, Mohan; Shaik, Bajivali; Kammela, Prasada Rao
ABSTRACT: A highly efficient and simple protocol for the construction of aromatic and aliphatic isothiocyanates from their respective amines in the presence of cheap, readily available, and air-stable cobalt catalyst is described. All reactions were carried out under optimized reaction conditions and gave target products in good to excellent yields within shorter reaction time. GRAPHICAL ABSTRACT: